The effect of feeding methods and non-nutritive sucking habits on early childhood caries and development of occlusion (A cross-sectional study) - Huda R. Awsi; Bayan A. Hassan (Erbil Dental Journal)
Background and objectives: Early Childhood Caries (ECC ) is the most common chronic disease conditioning childhood and involves the presence of one or more decayed (noncavitated or cavitated lesions),missing(due to caries), or filled tooth surfaces in children under 72 months of age.Time and frequency of breast-feeding, artificial feeding and of non-nutritive sucking habits can influence orofacial development, and when negative can provoke instability of orofacial function. Sucking habits involving digits or dummies are the most tangible environmental factors that play a role in the etiology of malocclusion. Subjects and method: A cross sectional study performed on aconvenient samples of 500 preschool child renaged between 4-6 years old in Erbil city. Parents (mothers ) were asked for a permission to include their children in the study. A short interview with the mothers of the children preceded the dental examination. The clinical examination included child weight, height determination and dental examination. Results: The results showed that prevalence of caries in breast fed children was (70.6%), in bottle was (62.4%) and both fed children was (65%) with no significant association between type of feeding and caries prevalence (P=0.298). Mean dmfs in males was (9.84±12.99) which is higher than mean dmfs of females (7.39 ±10.58). Class II canine classification was higher in bottle and both feeding than in breast feeding and there was no prevalence of Class III canine relation was found in bottle feeding. Conclusion: Type of feeding was not found to be related to development of early childhood caries in primary dentition of preschool children. Bottle feeding was considered as a risk factor for development of class II canine relation. Non-nutritive sucking (finger, pacifier sucking and both) were found to be risk factors for the development of anterior open bite and posterior cross bite. Finger sucking produces the development of unilateral posterior cross bite in primary dentition.